2021
DOI: 10.1007/s12013-020-00959-6
|View full text |Cite
|
Sign up to set email alerts
|

CLIC1 Inhibition Protects Against Cellular Senescence and Endothelial Dysfunction Via the Nrf2/HO-1 Pathway

Abstract: Chloride intracellular channel 1 (CLIC1) is a sensor of oxidative stress in endothelial cells (EC). However, the mechanism by which CLIC1 mediate the regulation of endothelial dysfunction has not been established. In this study, overexpressed CLIC1 impaired the ability of the vascular cells to resist oxidative damage and promoted cellular senescence. Besides, suppressed CLIC1 protected against cellular senescence and dysfunction in Human Umbilical Vein Endothelial Cells (HUVECs) through the Nrf2/HO-1 pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…The NRF2 pathway plays a critical role in the anti‐oxidative effect during cellular senescence and apoptosis. 46 , 47 , 48 NRF2 phosphorylation and nuclear translocation was reduced in BGC823 and GES‐1 cells caused by propofol stimulation in the current study, leading to decrease the binding of NRF2 to AR promoter. Interestingly, KEAP1 served as a cytoplasmic factor that interacted with the Neh2 domain and formed the KEAP1‐NRF2 complex to sequester NRF2 in the cytoplasm and initiate degradation of NRF2 by ubiquitination and proteasomal degradation unless there is a stress stimulus around.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The NRF2 pathway plays a critical role in the anti‐oxidative effect during cellular senescence and apoptosis. 46 , 47 , 48 NRF2 phosphorylation and nuclear translocation was reduced in BGC823 and GES‐1 cells caused by propofol stimulation in the current study, leading to decrease the binding of NRF2 to AR promoter. Interestingly, KEAP1 served as a cytoplasmic factor that interacted with the Neh2 domain and formed the KEAP1‐NRF2 complex to sequester NRF2 in the cytoplasm and initiate degradation of NRF2 by ubiquitination and proteasomal degradation unless there is a stress stimulus around.…”
Section: Discussionsupporting
confidence: 48%
“…The NRF2 pathway plays a critical role in the anti-oxidative effect during cellular senescence and apoptosis. [46][47][48]…”
Section: Discussionmentioning
confidence: 99%
“…OxS might be an interesting therapeutic target to modulate senescence. Results from various experimental models have demonstrated that the inhibition of OxS can effectively inhibit cellular senescence [92][93][94]173]. The same has been shown in the aging liver: a number of in vivo studies have demonstrated the attenuation of hepatic senescence by preventing ROS production or by enhancing the antioxidant response [174][175][176].…”
Section: Targeting Oxidative Stress To Modulate Cellular Senescencementioning
confidence: 86%
“…The Kelch-like ECH-associated protein 1-(Keap1-) nuclear factor-erythroid 2-related factor 2 (Nrf2) (Keap1-Nrf2) pathway has been described as a mediator between OxS and senescence, since it attenuates the effects of ROS and regulates downstream senescence-associated pathways [91]. The modulation of cellular senescence by Nrf2 activation has been explored in various other experimental models, demonstrating that impairment of this pathway mediates OxS-induced senescence and that activation of this pathway inhibits cellular senescence in vitro and in vivo [92][93][94]. Additional studies should be performed to confirm the role of the Nrf2 pathway in the regulation of cellular senescence in the context of NAFLD.…”
Section: Molecular Mechanisms Of Oxidative Stress Contributing To Sen...mentioning
confidence: 99%
“…Intracellular chloride channel 1 (CLIC1) is an oxidative stress sensor in endothelial cells. CLIC1 overexpression inhibits Nrf2 nuclear translocation, contributing to the hydrogen peroxide-induced activation of mitochondrial fission in human umbilical vein endothelial cell functional impairment [ 74 ]. Zhu et al [ 34 ] found that Nrf2 activation inhibits Drp1-mediated mitochondrial fission, improving endothelial dysfunction.…”
Section: Nrf2 Suppresses Endothelial Dysfunction By Improving Mitocho...mentioning
confidence: 99%